2017
DOI: 10.1177/0885066616686035
|View full text |Cite
|
Sign up to set email alerts
|

Safety of the Peripheral Administration of Vasopressor Agents

Abstract: Vasopressors are an integral component of the management of septic shock and are traditionally given via a central venous catheter (CVC) due to the risk of tissue injury and necrosis if extravasated. However, the need for a CVC for the management of septic shock has been questioned, and the risk of extravasation and incidence of severe injury when vasopressors are given via a peripheral venous line (PVL) remains poorly defined. We performed a retrospective chart review of 202 patients who received vasopressors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
126
1
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(144 citation statements)
references
References 22 publications
(28 reference statements)
4
126
1
13
Order By: Relevance
“…[10] This study suggested that the administration of vasopressors through a CVC may not be a necessity for all patients. [10] In a 6-month pilot study, phenylephrine was administered via PIV access in 20 patients with one minor complication and no major injuries. [11] This was achieved by implementing safety measures in the computerized physician order entry system (CPOE) and by utilizing nurse-driven protocols.…”
Section: Review Of the Literaturementioning
confidence: 89%
See 2 more Smart Citations
“…[10] This study suggested that the administration of vasopressors through a CVC may not be a necessity for all patients. [10] In a 6-month pilot study, phenylephrine was administered via PIV access in 20 patients with one minor complication and no major injuries. [11] This was achieved by implementing safety measures in the computerized physician order entry system (CPOE) and by utilizing nurse-driven protocols.…”
Section: Review Of the Literaturementioning
confidence: 89%
“…A retrospective chart review of vasopressor administration through a PIV catheter demonstrated a 4% overall incidence of extravasation events when a strict safety protocol was not in place. [10] None of these events were severe enough to require intervention and vasopressors were resumed in a new peripheral site most of the time. [10] This study suggested that the administration of vasopressors through a CVC may not be a necessity for all patients.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Norepinephrine was used in 50 of 55 cases, with local extravasation in two patients and one patient developing thrombophlebitis. Another retrospective observational study used data from 202 patients, admitted to the ICU of an academic teaching hospital, who received vasopressor infusion via a PVC . In this cohort, with 73% of patients diagnosed with septic shock, the majority (72%) received norepinephrine and extravasation events occurred in 4% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the common practice of requiring central venous access for vasopressor infusion hampered early use of vasopressors. 34,35 However, current data suggest that norepinephrine administration through large peripheral intravenous catheters for short intervals (hours to days) with appropriate monitoring is safe, 3637 facilitating early vasopressor use for sepsis resuscitation.…”
Section: Restrictive Fluids Approachmentioning
confidence: 99%